(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Limited access to completed research outputs remains a common challenge among senior high school students, especially in public school divisions where research papers are often stored manually, kept in separate schools, or made available only through limited physical archives. This study aimed to design, develop, and evaluate a web-based Research Repository System that would promote greater research accessibility within the Alaminos City Division. Specifically, the study sought to provide a centralized and secure digital platform where approved research papers could be uploaded, organized, searched, and retrieved by authorized users such as students, teachers, and research coordinators. The study employed a descriptive-developmental research design. The developmental aspect focused on the planning, design, coding, testing, and deployment of the repository system, while the descriptive aspect involved evaluating the quality and acceptability of the system based on the ISO/IEC 25010 software quality model. The system was assessed in terms of functionality, performance efficiency, usability, reliability, and security. Data were gathered from selected evaluators who examined the system’s features, ease of use, response time, dependability, and protection of stored research documents. Results showed that the developed Research Repository System received excellent ratings across the evaluated software quality criteria. The system was found to be functional, user-friendly, efficient, reliable, and secure. These findings indicate that the proposed system can effectively address the problem of limited research access by providing a structured, accessible, and sustainable digital archive for completed senior high school research outputs. In conclusion, the web-based Research Repository System supports improved research engagement by making previous studies easier to locate and use as references. It also helps strengthen research culture, knowledge sharing, and academic collaboration within the Alaminos City Division.